The Protection of Agricultural Land in Denpasar Seen From Legal Aspects of Agricultural and Spatial Planning - Sarna, Kadek (Journal of Food Security and Agriculture, 2017)
The land area in Denpasar until the end of 2009 is an area of 12 728 ha and for approximately the past five years this vast wetland is reduced by approximately 283 hectares or shrink an average of approximately 2.8% per year. For 2014 to 2015, has also been a shrinking agricultural land is large enough that an area of 30 hectares. The decline in agricultural land in Denpasar and in Bali is generally part rampant land conversion is happening today. No PERDA Denpasar governing the protection of agricultural land, it becomes very worrisome, given the legal certainty in order to maintain the quality and quantity of agricultural land as an effort to maintain the carrying capacity and environmental sustainability. By using a legal research methods juridical empirical approach to legislation (statue approach), the fact (fact approach) and the conceptual approach (analytical conceptual approach), will now be studied forms of law enforcement, barriers, and the efforts that have been applied in ensuring the sustainability of land agriculture by the government of Denpasar. The conclusion is the Form of law enforcement and the protection of agricultural land in the municipality of Denpasar is shaped law enforcement of preventive and repressive. Barriers in ensuring the sustainability of agricultural land in the municipality of Denpasar is still not the Detail Spatial Plan Areas and the arrangement of zoning both Bali Provincial and District / Municipal Especially Denpasar, and the efforts that have been applied in ensuring the sustainability of agricultural land by the government of Denpasar is to establish rules incentives in the form of agricultural land.